Cytokinins modulate auxin-induced organogenesis in plants via regulation of the auxin efflux - Pernisová, Markéta; Klíma, Petr; Horák, Jakub; Válková, Martina; Malbeck, Jirí; Soucek, Premysl; Reichman, Pavel; Hoyerová, Klára; Dubová, Jaroslava; Friml, Jirí; Zazímalová, Eva; Hejátko, Jan (Proceedings of the National Academy of Sciences of the United States of America, 2009)
Postembryonic de novo organogenesis represents an important competence evolved in plants that allows their physiological and developmental adaptation to changing environmental conditions. The phytohormones auxin and cytokinin (CK) are important regulators of the developmental fate of pluripotent plant cells. However, the molecular nature of their interaction(s) in control of plant organogenesis is largely unknown. Here, we show that CK modulates auxin-induced organogenesis (AIO) via regulation of the efflux-dependent intercellular auxin distribution. We used the hypocotyl explants-based in vitro system to study the mechanism underlying de novo organogenesis. We show that auxin, but not CK, is capable of triggering organogenesis in hypocotyl explants. The AIO is accompanied by endogenous CK production and tissue-specific activation of CK signaling. CK affects differential auxin distribution, and the CK-mediated modulation of organogenesis is simulated by inhibition of polar auxin transport. CK reduces auxin efflux from cultured tobacco cells and regulates expression of auxin efflux carriers from the PIN family in hypocotyl explants. Moreover, endogenous CK levels influence PIN transcription and are necessary to maintain intercellular auxin distribution in planta. Based on these findings, we propose a model in which auxin acts as a trigger of the organogenic processes, whose output is modulated by the endogenously produced CKs. We propose that an important mechanism of this CK action is its effect on auxin distribution via regulation of expression of auxin efflux carriers.
Keywords: kyseliny indoloctové; Cytokinins; signální transdukce; Signal Transduction; Arabidopsis; Indoleacetic Acids; biologický transport; Plant Roots; kořeny rostlin; Biological Transport; cytokininy